Laryngeal stenosis in a patient with severe congenital neutropenia1. (24th May 2012) - Bando, Hideki; Nagao, Hikaru; Nishio, Takeshi; Hirota, Ryuichi; Sakaguchi, Hirofumi; Imamura, Toshihiko; Hisa, Yasuo
Abstract: Objectives/Hypothesis: We report the first case of laryngeal stenosis with granuloma in a patient with severe congenital neutropenia (SCN). Study Design: Case report and retrospective review. Methods: Review of medical records. Results: A 6‐year‐old female who was diagnosed with SCN presented with a cough and wheezing. An endoscopic study revealed laryngeal stenosis with granuloma. Tracheotomy and direct laryngoscopy were performed under general anesthesia, and administration of granulocyte colony‐stimulating factor was started. The laryngeal granuloma disappeared 3 weeks later, and the tracheal stoma was closed. Conclusions: Presence of a laryngeal lesion should be considered in SCN patients with persistent airway symptoms.